THE EFFICIENT USE OF HUMAN RESOURCES IN RUSSIA IN CONDITIONS OF CATCHING-UP DEVELOPMENT - G. Ryazanova; P. Tolkachev (Вестник университета)
The relationship of labor productivity with other macroeconomic indicators has been analyzed: the level of wages in current prices and taking into account the Paasche deflator index; dynamics of the gross domestic product; the dynamics of the share of food in the consumer basket; the indicators of changes in clean investments, that is a key factor in economic growth in the national economy. On the basis of empirical data, the trends of productivity growth in comparison with the growth of other macroeconomic indicators algebraically and graphically have been shown. It has been concluded, that the development of human resources is necessary, since low productivity is a brake on the economic growth of the country in the conditions of catching-up development.